On a robust estimation of option-implied interest rates and dividend yields - Muoria Kamau; Ivivi Joseph Mwaniki (Cogent Economics & Finance, 2023)
In this paper, a simple no-arbitrage methodology to estimate option-implied interest rates and dividend yields simultaneously via a regression model is employed. Since the mean-based least squares estimation places equal weights on all data points making it sensitive to outliers, a robust median-based estimation approach is proposed. The proposed methodology is only valid for European options; consequently, an empirical analysis is conducted on options on the S & P 500 Index. Robust forward-looking model-free estimates of the risk-free interest rate and dividend yield, based exclusively on market prices of options, are thus obtained.
Keywords: 330; box spread; implied dividend yield; implied interest rates; no-arbitrage; option-implied; repeated median; risk-free rate; sloped asset position; Theil-Sen